The spatiotemporal pattern of digital infrastructure development level in China - Jianjun, LIU; Dapeng, LIANG (Zi yuan ke xue, 2025)
[Objective] Digital infrastructure serves as a sustained driving force for the formation of new-quality productive forces. This study aims to reveal the spatiotemporal evolution, regional disparities, and spatial convergence characteristics of digital infrastructure development in China. This is of great significance for promoting balanced regional development and empowering high-quality growth, and thereby driving the development of new productive forces. [Methods] Using China’s provincial panel data from 2013 to 2022, an indicator evaluation system for digital infrastructure construction and application was established. Methods such as the entropy method, Theil index, convergence models, two-way fixed effects models, and spatial econometrics were employed to conduct an in-depth analysis of the spatiotemporal evolution, regional disparities, and spatial convergence of digital infrastructure. [Results] (1) The level of digital infrastructure development in China exhibited an overall upward trend, but there are spatial differences. It shows a spatial distribution pattern where the eastern region has a higher level, while the western and northeastern regions are relatively lower. (2) The overall differences in the development level of digital infrastructure are gradually narrowing. The differences are shifting from being mainly between regions to being more pronounced within regions. The regional differences within regions show a hierarchical structure of “eastern > western > central > northeastern”. (3) In terms of convergence characteristics, a gradually weakening trend was observed in the convergence of China’s digital infrastructure development level. Both national and regional levels of digital infrastructure development demonstrated spatial conditional convergence, with convergence speeds ranked as follows: the central region was th e fastest, followed by the western and eastern regions, while the northeastern region was the slowest. [Conclusion] Bridging the gaps in digital infrastructure development, reducing regional disparities, and strengthening cross-regional collaboration are key to balanced regional development. This study provides theoretical support and practical guidance for promoting the convergent development of regional digital infrastructure and formulating tailored policies based on regional conditions.